Retrospective Analysis of N75-P100 Amplitudes and P100 Latencies of VEPs in Patients Having One-Sided Visual Problems (International Journal of Physiology, 2019)
BackgroundVEPs of patients who had unilateral visual problems were retrospectively analyzed. The patients N75-P100 amplitudes and P100 latencies of the affected and normal fellow eye were compared. An alternative way of percentage change in amplitude and latency was also correlated with existing (amplitude ratio and absolute prolongation of latency) ways of analysis.Method66 subjects (52 males & 14 Females) selected for study who had either affected left or right eye. Further, mean of N75-P100 amplitudes & mean P100 latencies were compared in affected and normal eye. On the basis of percentage reduction in the N75-P100 amplitude and percentage increase in the P100 latency on affected eye subjects were categorized in to those only with reduced amplitude (Group A), only with increased latency (Group B) or with both reduced amplitude & increased latency (Group C).ResultsOut of 66 patients (mean age 39.50±19.06 yr), 52 were males (78.79%, mean age 38.04±19.22 yr) & 14 were females (21.21%, mean age 44.93±18.11 yr). The patients had nearly equal frequency of affection in right and left eye, with slight preponderance to left eye (LE-n= 38, 57.58%; RE-n= 28, 42.42%). The amplitude reduction (p